Functional activity but not gene expression of toll-like receptors is decreased in the preterm versus term human placenta - Aled Bryant (Placenta, 2015)
INTRODUCTION: Toll-like receptor (TLR) activity within gestation-associated tissues might have a role in normal pregnancy progression as well as adverse obstetric outcomes such as preterm birth (PTB). METHODS: The expression and activity of TLRs 1 – 9 in placentas collected following preterm vaginal delivery after infection-associated preterm labour (IA-PTL) at 25 – 36 weeks of gestation (preterm-svd, n = 10) were compared with those obtained after normal vaginal delivery at term (term-laboured; n=17). Placental explants were cultured in the presence of agonists for TLR2, 3, 4, 5, 7, 8 and 9 and cytokine production after 24 hours examined. Expression of TLR transcripts was determined using real time quantitative PCR. RESULTS: Reactivity to all agonists except CpG oligonucleotides was observed indicating that other than TLR9 all of the receptors studied yielded functional responses both term and preterm. Significantly less TNFα and IL-6, but not IL-10, were produced by preterm than term samples in response to all TLR agonists. Changes in TLR mRNA expression did not underlie functional differences in the preterm and term groups; nor does a pre-exposure/tolerance model mimic this finding. While glucocorticoids suppressed cytokine production in an in vitro model using term tissue the association between lower gestational age and decreased cytokine outputs suggests a temporally regulated response. DISCUSSION: Pro-inflammatory cytokine output in response to multiple TLR ligands was decreased in the preterm compared to the term placenta but gene expression for each TLR tended to be similar. Reduced cytokine production by the preterm placenta in response to stimulation of TLRs therefore must be regulated at the post-transcriptional level in a gestational age dependent manner.